2007
DOI: 10.2337/dc06-1964
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Insulin Therapy in Critical Care

Abstract: OBJECTIVE -To review performance characteristics of 12 insulin infusion protocols.RESEARCH DESIGN AND METHODS -We systematically identify and compare 12 protocols and then apply the protocols to generate insulin recommendations in the management of a patient with hyperglycemia. The main focus involves a comparison of insulin doses and patterns of insulin administration.RESULTS -There is great variability in protocols. Areas of variation include differences in initiation and titration of insulin, use of bolus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(113 citation statements)
references
References 50 publications
0
107
0
6
Order By: Relevance
“…This result also requires a level of adaptability from the TGC protocol that is not available in most published cases [66,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result also requires a level of adaptability from the TGC protocol that is not available in most published cases [66,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…• Insulin sensitivity (S I hereafter) and its variability, which controls the balance between the first two factors (insulin and nutritional inputs) and outcome glycemia for a given set of these two interventions A typical TGC control protocol controls only insulin dosing [42,66,77,81], excepting SPRINT, which (uniquely) controls both insulin and nutrition individually. Many studies leave nutritional inputs to unit specific standards and don't specify or report them.…”
Section: Insulin Sensitivity Patient Variability and Impact On Tgcmentioning
confidence: 99%
“…A review of 12 published insulin infusion protocols for critically ill patients showed wide variability in dose recommendations and variable glucose control [485]. This lack of consensus about optimal dosing of IV insulin may reflect variability in patient factors (severity of illness, surgical versus medical settings), or practice patterns (e.g., approaches to feeding, IV dextrose) in the environments in which these protocols were developed and tested.…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…Les protocoles d'insuline 22,23 Standardisation La standardisation de l'insulinothérapie intraveineuse améliore l'efficacité et l'innocuité des stratégies de contrôle de la glycémie comparativement à une titration dirigée par le médecin. 24 Bien qu'il n'existe que peu de données qui permettent de comparer la performance de différents protocoles, un indice de pénalité glycémique 25 récemment mis au point pourrait faciliter de telles évaluations.…”
Section: Impact Cliniqueunclassified
“…Insulin protocols 22,23 Standardization Standardization of intravenous insulin therapy improves the efficiency and safety of glucose control strategies when compared with physician-directed titration. 24 While little data exist to compare the performance of different protocols, a recently developed glycemic penalty index 25 may facilitate such evaluations.…”
Section: Clinical Impactmentioning
confidence: 99%